Managerial Media Ecology: Employing the Multidisciplinary Humanities for Leadership and Management Communication - Gustafson, Erik; Rodgers, John (New Explorations, 2025)
The humanities are lauded as essential topics of study for individuals seeking a well-rounded education that will serve them in a litany of fields. However, the humanities are often relegated to the status of “soft skills” based on the notion that they are antiquated, irrelevant, and less necessary than “hard” technical competencies. The present article sought to address this perceptual gap by demonstrating how the humanities – specifically, the field of media ecology – can be integrated with particular tenets of management and leadership communication. To accomplish this task, the present article provided an overview of the key tenets of media ecology, offered a review of select perspectives in managerial and leadership communication, and demonstrated how the two seemingly disparate fields could be intertwined in order to create more well-rounded communicators in the workforce. Broad implications are drawn for media ecology, leadership communication, and the further preservation and advancement of the humanities in the 21st century.